Heat transfer characterization of a new collector design featuring ribs, petals, and helical twisted tapes: Experimental study - Banw Omer Ahmed; Adnan Ibrahim; Hariam Luqman Azeez; Sharul Sham Dol; Ali H.A. Al-Waeli; Mahmoud Jaber (Case Studies in Thermal Engineering)
The limited thermal efficiency of collectors in photovoltaic thermal systems continues to pose a major hurdle. This study tackles the issue by developing an innovative collector featuring a rib and petal arrangement, combined with a helical twisted tape and channelling silicon carbide-enhanced nanofluids at volume concentrations of 0.3 %, 0.6 %, and 0.9 %. Thermohydraulic Performance analysis evaluates five absorber tubes: a smooth tube, a ribbed and petaled tube, and versions with added coil, twisted tape, and both coil and twisted tape. The study also examines the thermal efficiency of the corresponding collectors of each absorber tube. Flow rates of 0.01–0.085 kg/s, a heat flux and solar irradiances of 400 W/m2, and varying concentrations of nanofluid are the primary conditions of the experiments. Results indicate that mass flow rate positively correlates with the Nusselt number and thermal efficiency but negatively correlates with the Friction Factor and Thermohydraulic Performance Factor. The new design of this study records a maximum Thermohydraulic Performance enhancement of 1.5 times compared to a smooth tube and an optimal thermal efficiency enhancement of 20.4 % in comparison to a smooth tube collector. In the best case, there is a decline of 50.1 % in the Thermohydraulic Performance Factor and an increase of 10.2 % in thermal efficiency when the mass flow rate increases.